Optimization of delignification process from red meranti wood sawdust pretreated with acidified sodium chlorite - Siti Noredyani, Abdul Rahman; Zularisam, Ab Wahid; Noormazlinah, Ahmad; Mimi Sakinah, Abdul Munaim (Springer, 2020)
Delignification is a process to remove the lignin content from lignocellulosic biomass to increase hydrolysis efficiency. In other word, the process ensure cellulose parts are more accessible. In the present research, there were two objectives; i) to optimize the operating parameters of acidified sodium chlorite pretreatment for delignification of RMWS, and ii) to characterize the RMWS that used as feedstock. The two significant variables, reaction time and ratio of sodium chlorite to sawdust were optimized using response surface methodolog and experiments were performed according to a central composite experimental design in order to enhance the delignification process as well as holocellulose recovery. The experimental design was expressed based on preliminary work and screening process using the combined severity, which ranged from 0.76 to 1.64 for chlorite solution and temperature range from 65°C to 85°C. The experimental results showed the optimal condition of acidified pretreatment of RMWS were 1.2 for the ratio of sodium chlorite to RMWS at an optimal temperature of 75°C, resulted in 79.6% holocellulose recovery and 97.33% of lignin removal. These results are important for further treatment to finally extract the cellulose.